2019
DOI: 10.2136/vzj2018.12.0211
|View full text |Cite
|
Sign up to set email alerts
|

Microhydrological Niches in Soils: How Mucilage and EPS Alter the Biophysical Properties of the Rhizosphere and Other Biological Hotspots

Abstract: Core Ideas Plant mucilage and bacterial extracellular polymeric substances (EPS) prevent the breakup of the soil liquid phase. Formation of continuous structures buffers soil hydraulic properties. The release of viscous polymeric substances represents a universal strategy. Plant roots and bacteria are capable of buffering erratic fluctuations of water content in their local soil environment by releasing a diverse, highly polymeric blend of substances (e.g. extracellular polymeric substances [EPS] and mucilag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
92
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 55 publications
8
92
1
Order By: Relevance
“…Here, the presence of mucilage is assumed to have two contrasting effects on the K *(θ). Due to increasing the viscosity of the liquid phase it reduces the K *(θ) but as soil dries it avoids big drop in K *(θ) by maintaining the connectivity f liquid phase (Benard et al, 2019). With increasing mucilage concentration in the liquid phase, the viscosity of the liquid phase increases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the presence of mucilage is assumed to have two contrasting effects on the K *(θ). Due to increasing the viscosity of the liquid phase it reduces the K *(θ) but as soil dries it avoids big drop in K *(θ) by maintaining the connectivity f liquid phase (Benard et al, 2019). With increasing mucilage concentration in the liquid phase, the viscosity of the liquid phase increases.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the physical properties of mucilage collected from plant seedlings were shown to be plant specific and concentration dependent, which makes it challenging to select a mucilage representative of mucilage across plant species. However, besides these variations, all mucilages showed unique intrinsic physical properties: reduction of surface tension of the soil solution, increase of viscosity, increase of the water holding capacity, and turning hydrophobic as they dry (Benard et al, 2019).…”
mentioning
confidence: 99%
“…Rhizosheaths are proposed to form and be stabilised through the action of soil particle entanglement with root hairs and adhesive mucilage; however, the adhesive molecules at root surfaces have not been identified and structurally elucidated (Brown et al, 2017;Pang et al, 2017). Plant factors released into soil are likely to have a wide range of functions that would include altering soil biophysical factors, soil particle aggregation, and the generation of microhydrological and microbiotic niches (Guinel and McCully, 1986;Watt et al, 1993;Knee et al, 2001;Naveed et al, 2017;Benard et al, 2019). Factors involved in the maintenance of rhizosheaths may increase soil quality in general by increasing water flow, and thus nutrient flow and soil aeration through more frequent pores (Tisdall and Oades, 1982;Benard et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Plant factors released into soil are likely to have a wide range of functions that would include altering soil biophysical factors, soil particle aggregation, and the generation of microhydrological and microbiotic niches (Guinel and McCully, 1986;Watt et al, 1993;Knee et al, 2001;Naveed et al, 2017;Benard et al, 2019). Factors involved in the maintenance of rhizosheaths may increase soil quality in general by increasing water flow, and thus nutrient flow and soil aeration through more frequent pores (Tisdall and Oades, 1982;Benard et al, 2019). During periods of drought, some grasses can increase the thickness of their rhizosheath, potentially in an effort to secure water uptake (Watt et al, 1994;Rabbi et al, 2018;Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…They found that the capacity of these substances to stabilize soil particles depends on their deformation capacity. In addition, mucilage dynamically modifies mechanical properties of the soil matrix such as the penetration resistance (Haas and Horn) and hydraulic properties of the soil solution (Benard et al, 2019). While the importance of mucilage for rhizosphere hydration and root growth is wellrecognized (Carminati et al, 2011), direct measurements of mucilage in intact soils remain challenging.…”
Section: Rhizosphere Functioning and Structural Development As Complementioning
confidence: 99%